Characterizing groundwater – surface water interaction across the Brazos River watershed, Texas, with uranium isotopes. (December 2022) - Prince, Benjamin H.; Marcantonio, Franco; Knappett, Peter S.K.
Abstract: 234 U/ 238 U activity ratios and uranium concentrations were measured over a 6-month period in the Brazos River watershed along the Brazos River Alluvial Aquifer to determine the proportion of variable sources supplied to the Brazos River. Results indicate that lithology within the Brazos River watershed substantially impacts uranium isotope systematics as the composition of the underlying bedrock changes from carbonate to siliciclastic rocks downstream. Rain was found to have a negligible effect on 234 U/ 238 U activity ratios within water sources in the study area, and only dilutes the bulk concentration of uranium in these sources. 234 U/ 238 U activity ratios and uranium concentrations suggest water in the Brazos River near Bryan/College Station, Texas, is sourced from Lake Whitney, groundwater, and small tributaries entering the stretch of river investigated. Groundwater appears to discharge from the shallow alluvial aquifer to the river at a steady rate with slight increases in groundwater contributions as the Brazos River water discharge increases. Highlights: 234 U/ 238 U activity ratios in surface waters and groundwaters of the Brazos River, Texas, watershed. Water sources to the Brazos River are quantified (tributaries versus lake versus groundwater from alluvial aquifer). Groundwater discharges into river at steady state; increases in groundwater contribution as river water discharge increases.